Development of a Culinary Business Strategy for Fruit and Vegetable Juice Drinks “Fresh Healthy Juice” With a Swot Analysis Approach and Business Model Canvas - Indra, Agustian; Herlinawati, Erna (Dinasti International Journal of Digital Business Management, 2025)
Public awareness of the importance of a healthy lifestyle has driven the growth in consumption of fresh fruit and vegetable-based beverages. This study aims to develop a business strategy for the “Fresh Healthy Juice” culinary business using a SWOT analysis and Business Model Canvas (BMC) approach. The research method used is qualitative descriptive, with data collection through interviews, observations, and literature reviews. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats affecting the business, while BMC is used to design an adaptive and innovative business model. This study aims to formulate a business development strategy for the Fresh Healthy Juice fruit and vegetable beverage business using a SWOT analysis and Business Model Canvas (BMC) approach. The main challenges faced by this business include sales instability due to high competition, limited product shelf life, and a lack of innovation in digital marketing. The research was conducted through direct observation, interviews with business owners, and documentation of business activities. SWOT analysis was used to identify internal and external factors of the company, while BMC helped in mapping the nine main elements of the business model. The analysis results show that Fresh Healthy Juice has strengths in the use of natural ingredients without preservatives, a healthy brand image, and hygienic processing. Significant opportunities were also identified, including the growing trend toward healthy lifestyles, potential collaborations with related businesses, and advancements in digital marketing. Based on the SWOT matrix results, the business is positioned in Quadrant I, indicating the need for an aggressive strategy (S–O) to optimize strengths in capitalizing on opportunities. The recommended strategies include: strengthening branding, expanding through digital platforms. With the implementation of the right strategies, Fresh Healthy Juice has the potential to increase its competitiveness and expand its market share sustainably. This study provides strategic recommendations for creating a sustainable and competitive business model, while also serving as a guide for small and medium-sized businesses in the healthy food sector to navigate the ever-changing market dynamics.